Accipiter gentilis geometry from Raptor wing morphing with flight speed - Jorn A. Cheney (9502913); Jonathan P. J. Stevenson (9502916); Nicholas E. Durston (9502919); Masateru Maeda (2577082); Jialei Song (3289029); David A. Megson-Smith (11051285); Shane P. Windsor (9502928); James R. Usherwood (9502922); Richard J. Bomphrey (9502925) (2021)
stl geometry of Accipiter gentilis units metres